Musicality of a Literary Work - Hejmej, Andrzej (Literary and Cultural Theory, 2018)
This book represents an attempt to capture different links between modern literature and music. The author examines strict intertextual correlations, the phenomena of musicality and musicality of literary works, the musical structure in literature, so-called musical literary texts. He focuses on the novel Le Cœur absolu by Philippe Sollers, the poem Todesfuge by Paul Celan, the Preludio e Fughe by Umberto Saba and the drama Judasz z Kariothu [Judas Iscariot] by Karol Hubert Rostworowski. The analysis also includes Stanisław Barańczak's cycle of poems Podróż zimowa: Wiersze do muzyki Franza Schuberta [Winter Journey: Poems to the Music of Franz Schubert] and a fragment of Scène from Hérodiade by StéphaneMallarmé in Paul Hindemith's composition «Hérodiade» de Stéphane Mallarmé.